Assessment of Laptop Ergonomic Practices and Their Association with Work-Related Musculoskeletal Disorders Among Office Employees: A Cross-Sectional Study - MUHAMMAD AKMAL,; Muhammad Ajmal ,; Muhammad Afzal,; Muhammad Ahsan Raza,; Muhammad Ahmed,; Mukhtiar Hussain , (Pakistan Journal of Medical & Health Sciences, 2025)
Background: The growing use of laptops in offices has given rise to emerging concerns that are related to the work-related musculoskeletal disorders (WMSDs). Lack of proper ergonomic procedures, extended sitting and unsuitable work stations setups are some of the determinants of musculoskeletal overloads among employees. This project used the assessment of the laptop ergonomics practice and tested its relationship with WMSDs among office employees working in various organizations in Saudi Arabia, Pakistan, and China. Methods: It involved a cross-sectional study with 70 full-time employees working in the office and using laptops at least three hours a day during the period between April 2023 and April 2024. The participants were recruited at Alostool Al Aali, Arabian Safety Training Institute, Saudi Electric Service Polytechnique, Ar Razi Medical Complex, Shaikha Fatima institute of nursing and health science, and Jining medical university. The structured questionnaire that was used to gather data included demographic information, a checklist on the ergonomics of the laptop, and the Standardized Nordic Musculoskeletal Questionnaire. The SPSS version 26 was used to perform descriptive statistics, chi-square tests, and logistic regression, and p < 0.05 was deemed statistically significant. Results: WMSDs were widespread, 68.6% and most affected areas were the neck (55.7), lower back (50.0) and shoulders (42.9). It was noted that in 71.4% of the participants, poor ergonomic practices were included. Ergonomic poor practices were significantly associated with WMSDs (p < 0.01). The rate of discomfort was reported to increase in employees spending more than six hours a day working with laptops and exhibited a protective effect with the use of external accessories. Conclusion: The prevalence of WMSDs is very high in office workers and is closely associated with improper ergonomics of laptops. Musculoskeletal risk can be significantly decreased by improving workstation arrangements, spreading the idea of ergonomics, and frequent breaks.